Exploring visitors' perception towards sustaining coastal and fishery resources in Tinggi and Sibu Islands, Johor - Hamzah, Nur Amalina; Kamarulzaman, Nitty Hirawaty; Abd. Latif, Ismail; Md. Yusof, Fatimah (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Tourism in Malaysia has been recognized for its natural attraction and contribution to the economy. Malaysia has the most beautiful islands in the world with blue crystal clear water, peaceful villages, and stunning beaches. In 1994, the Marine Park Area (MPA) was developed by the government to protect and conserve natural beauty of these islands. In the last few years, the number of visitors’ arrival in the MPA has increased dramatically. The consistent growth of visitors visiting the MPA has led to increase pressures on the environment. Thus, this study was conducted to identify factors that influence awareness of visitors towards sustaining coastal and fishery resources in Tinggi and Sibu Islands, Johor. The data were collected using structured questionnaires from 165 respondents. The data were analyzed using descriptive analysis and factor analysis to achieve the research objective. The results indicated that three factors have been extracted from factor analysis namely visitors knowledge on sustainable resources, environmental preservation, and recreational activities which influenced the awareness of visitors towards sustaining coastal and fishery resources. This study recommended that all parties including government should have been participating in any related conservation programs.